The Relationship Between Wrist Flexibility and Arm Muscle Strength with the Accuracy and Speed of Smash for Badminton Athletes Universitas Pendidikan Indonesia (UPI) - Ardianto Rifki Purnama; Yopi Kusdinar; Kardjono Kardjono; Mulyana (Universitas Negeri Semarang, 2024)
This study aims to analyze the relationship between wrist flexibility and arm muscle strength with smash accuracy and speed in badminton athletes of Universitas Pendidikan Indonesia (UPI). In this study using descriptive methods with correlational techniques and the sample in this study amounted to 12 UPI Badminton UKM athletes.. Descriptive statistics show the average wrist flexibility of 99.16, arm muscle strength of 5.01, smash accuracy of 4.25, and smash speed of 103.83. The normality test results showed that the data were normally distributed (p> 0.05). Pearson correlation analysis showed a significant positive relationship between wrist flexibility and smash accuracy (r = 0.640, p = 0.025) and smash speed (r = 0.662, p = 0.019). Similarly, arm muscle strength was significantly associated with accuracy (r = 0.587, p = 0.045) and smash speed (r = 0.720, p = 0.008). However, the regression analysis results showed that these two variables together did not have a significant effect on smash accuracy (p = 0.081) but were significant on smash speed (p = 0.030). The results of this study underscore the importance of wrist flexibility and arm muscle strength in supporting smash performance, both in terms of accuracy and speed. Training that focuses on improving flexibility and arm muscle strength is recommended to help athletes improve the quality of their smashes, while still considering aspects of technique and coordination.